Towards a perceptual model of corporate entrepreneurial activity: a focus on the South African financial sector - Wood, Eric Anthony (My University, 2016)
Improved understanding of the entrepreneurial behaviours and motivations of employees would allow senior management of corporate entities a better understanding of their employees’ opportunity recognition processes, thereby guiding the provision of appropriate assistance and support of these processes in order to boost entrepreneurial activity. This research aimed to further academic understanding of the corporate entrepreneurial process and opportunity identification by employees within existing corporate entities. It investigated the influence of employee perceptions of their company’s corporate entrepreneurial building blocks, entrepreneurial alertness and meta-cognitive processing, on the extent and quality of opportunity recognition. The study focused on employees in the South African financial services sector. It proposed a model of corporate entrepreneurial activity and the individual, which attempted to combine current models of corporate entrepreneurial activity with current thinking around the individual’s entrepreneurial decision-making within the entrepreneurial process. The conceptual model aimed to add to the body of knowledge in terms of the entrepreneurial employee aspiring to fill the knowledge gap in terms of how they think and act within the corporate environment. It applied current theory, around the entrepreneurial individual, to the entrepreneurial employee. The employee’s perceptions of their company’s entrepreneurial building blocks was analysed, as were their perceptions of entrepreneurial alertness and meta-cognitive processing in stimulating corporate entrepreneurial activity within the company. A sample of 784 employees from 102 employers in the South African financial sector was examined. The conceptual model was analysed using hierarchical regression and structured equation modelling. A number of moderating influences on the model were examined using regression analyses. The integrative model showed that the entrepreneurial behaviour required of employees is primarily focused around entrepreneurial alertness and meta-cognitive processing. The central nature of entrepreneurial alertness, as portrayed in the mediation model, showed that employee entrepreneurial activity could only occur through entrepreneurial alertness. The entrepreneurially alert employee is able to make connections and identify opportunities that an employee who is not entrepreneurially alert is unable to do. It is only once the entrepreneurially alert employee has identified potential entrepreneurial ideas (by connecting the dots in terms of the business information gathered), that the meta-cognitive processing abilities of the employee are able to turn this potential entrepreneurial idea into a viable entrepreneurial opportunity. Entrepreneurial alertness can therefore be seen as the first step in the employee entrepreneurial process, after the establishment of the entrepreneurial building blocks set in place by the company. The mediation model showed the importance of employee perceptions of their company’s entrepreneurial building blocks. It is therefore not only important that the company put these entrepreneurial building blocks in place, as the precursor to employee entrepreneurial activity, but also that these entrepreneurial building blocks be adequately communicated to employees. Employee perceptions of these building blocks, not their physical existence, allow for the appropriate employee entrepreneurial behaviour necessary to produce the appropriate levels of entrepreneurial activity for their company. This mediation model was shown to have a number of moderating influences at both the individual and the company level.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in fulfilment of the requirements for the degree Doctor of Philosophy Johannesburg, 2015
Keywords: Entrepreneurship--South Africa--Mathematical models; Financial services industry--South Africa